Associations of Common ?-Thalassemia Mutations With ?-Globin Gene Frameworks in Northern Thailand - P Sanguansermsri; D Shimbu; R Wongvilairat; T Sanguansermsri (Universitas Gadjah Mada, 2004)
This study aimed to characterize polymorphism of the b-globin gene (framework) among common b-thalassemia mutations found in northern Thailand. Thirty-one homozygous b-thalassemia major patients admitted to Chiang Mai University Hospital were identified using direct DNA sequencing method. Among 15 patients with homozygous of codon 41/42 (-TCTT), eight were homozygous of framework 1 (FW1), one was homozygous of FW3A, and the remainders were heterozygousof FW1 and FW3A. The gene frequencies of FW1 and FW3A in the patients were 0.733 (22/ 30) and 0.267 (8/30), respectively. All 11 patients with homozygous of codon 17 (A-T) were homozygous of FW3A, while three patients with homozygous of intron 1 nt 1 (G-T) were homozygous of FW1. Both patients with homozygous of codon 71/72 (+A) were FW3A. In this report, the numbers of b-globin gene frameworks were restricted in each b-thalassemia mutation. This investigation may provide further information for the study of the evolution of common mutations causing b-thalassemia major in northern Thailand.